2022
DOI: 10.1016/j.jaad.2021.06.875
|View full text |Cite
|
Sign up to set email alerts
|

Mohs micrographic surgery for vulvar malignancies: A systematic review

Abstract: BCC, Basal cell carcinoma; BSC, basosquamous cell carcinoma; DFSP, dermatofibrosarcoma protuberans; DVT, deep vein thrombosis; EMPD, extramammary Paget disease; Gyn, gynecology; Gyn onc, gynecology oncology; n/a, not applicable; OBGYN, obstetrics and gynecology; Postop, postoperative; SCC, squamous cell carcinoma; VC, verrucous carcinoma. *Defect size was only reported in 2 cases. y In 3 of 107 cases, recurrence was not reported, and these were not included in the calculation of recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…13 Our patient is the first pigmented vulvar BCC case reported in the literature that has been treated with MMS, an efficacious method for all vulvar malignancies. 12 No recurrences of vulvar BCC have been reported with MMS. 12 In summary, we present a case of a pigmented BCC on the vulva of an immunosuppressed Hispanic patient following a 3-year delay in diagnosis, which was treated with MMS, and review the current literature of other cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 Our patient is the first pigmented vulvar BCC case reported in the literature that has been treated with MMS, an efficacious method for all vulvar malignancies. 12 No recurrences of vulvar BCC have been reported with MMS. 12 In summary, we present a case of a pigmented BCC on the vulva of an immunosuppressed Hispanic patient following a 3-year delay in diagnosis, which was treated with MMS, and review the current literature of other cases.…”
Section: Discussionmentioning
confidence: 99%
“…5 Treatment is usually wide local excision or Mohs micrographic surgery. 6 Radiation, laser therapy, and topical therapies, such as imiquimod have also been used with variable success. 7,8 Systemic chemotherapy is utilized in advanced disease.…”
Section: Extramammary Paget Diseasementioning
confidence: 99%
“…For example, reports available on use of MMS for select cases of SCC have found this may be an effective modality as a first-line therapy in select cases and in some treatment-refractory cases: 38 cases of vulvar SCC were treated with MMS with 4 reporting recurrence, however most cases were not early SCC, as the average tumor size was 18 mm and multiple had been treated with prior modalities including excision. 4 Unfortunately, prospective studies on MMS for early vulvar SCC are lacking. Future studies should focus on efficacy and patient-reported outcomes with use of other tissue-sparing modalities for early vulvar SCC.…”
mentioning
confidence: 99%